The role of the gender composition of performance feedback on peers in shaping persistence and performance - Sándor Katona; Anna Lovász (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We study the impact of the gender composition of a scoreboard on the persistence and performance of players in an online game. Players were randomly selected into eight groups, defined along two dimensions: they saw high or average scores on a scoreboard (score level), and within each of these, they saw either 3 male, 2 male and one female, 1 male and 2 female, or 3 female names associated with the scores (gender composition). Based on 1140 participants, we find that males are generally less responsive to performance information on other participants. Compared to the baseline of all male names on the scoreboard, females play fewer games when they see only female names, but more games when they see mixed gender names with high scores. Their performance (best score) increases significantly when they see at least one female name and high scores. This result is in line with the importance of female-specific reference points - or role models - in encouraging females' participation and higher performance in competitive settings. It supports the use of policies aimed at providing these, such as the introduction of female role models and the public acknowledgement of high performing females.
Keywords: I20; J16; J24; M54; 330; Gender Gaps; Competition; Performance Feedback; Gender Composition; Reference Point